Komunikasi Interpersonal dan Regulasi Emosi sebagai Prediktor Persepsi Hubungan Romantis pada Masa Dewasa Awal - Setiawati, Yuni; Pratikto, Herlan; Efendy, Mamang (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
The perception of romantic relationships is when individuals find meaning in a relationship that leads to emotional and physical bonds with their partner and efforts to build a long-term relationship. This study aims to determine the relationship between interpersonal communication and emotion regulation with the perception of romantic relationships among married couples. The research method used a correlational quantitative research method with a total of 139 participants selected through snowball sampling. The research scale uses the romantic relationship perception scale taken from Schaefer & Olson (1981), the interpersonal communication scale from Rubin et al. (1988), and the emotion regulation scale from Gratz & Roemer (2004). The research results indicate that there is a positive relationship between interpersonal communication and emotion regulation with the perception of romantic relationships. This means that the higher the interpersonal communication and emotion regulation, the higher the perception of romantic relationships. Conversely, if there is a decrease in interpersonal communication and emotional regulation, the perception of romantic relationships will also decline.